Sir Karl Popper Speech 1993 - Knowing About Not Knowing
A video documenting Sir Karl Popper’s visit to Prague, Czech Republic in order to receive the Honorary Doctorate from Charles University. The video contains two short interviews in which Sir Popper remembers his previous visits in the country and explains the meaning of open society in the Czech context. Speakers in the video are Dr. J. Fiala, Professor at Charles University, Dr. Cyril Höschl the Dean of Medical Faculty in Prague and George Soros, the Founder of the Central European University. Images of the former Czech President Václav Havel greeting Sir Popper appear in this short film.